Social Factors in the Latinization of the Roman West - Mullen, Alex (Oxford University Press, 2023)
Latinization is a strangely overlooked topic. Historians have noted it has been 'taken for granted' and viewed as an unremarkable by-product of 'Romanization', despite its central importance for understanding the Roman provincial world, its life and languages. This volume aims to fill the gap in our scholarship, along with its sister volumes, Latinization, Local Languages and Literacies in the Roman West and Languages and Communities in the Late-Roman and Post-Imperial Western Provinces, all outputs of the European Research Council-funded LatinNow project. Experts have been selected to create a multidisciplinary volume with a thematic approach to the vast subject, tackling administration, army, economy, law, mobility, religion (local and imperial religions and Christianity), social status, and urbanism. They situate the phenomena of Latinization, literacy, bi-, and multilingualism within local and broader social developments and draw together materials and arguments that have not before been coordinated in a single volume. The result is a comprehensive guide to the theme, which also offers original and more experimental work. The sociolinguistic, historical, and archaeological contributions reinforce, expand, and sometimes challenge our vision of Latinization and lay the foundations for future explorations.